IMPACT OF COVID-19 ON INDIAN ECONOMY - Tejinder Singh (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The paper is an attempt to examine the adverse effects meted out by still evolving pandemic COVID-19 on the overall GDP of the country for financial year 2019-2020 and 2020-2021.A reference is also being made to 2008-2009 situation, where the adversely affected sectors made a strong comeback in the succeeding year. The reduction in global growth rates by leading rating agencies in worst and best case is also being referred to in this paper. The paper also discusses the relief measures announced by the Government of India like the bailout package announced for the MSME sector, enhanced liquidity measures for the banking sector.